Common Ground: A Creative Exploration of Narratives of Connection Between People and Land in Scotland and Aotearoa / New Zealand - Gunn, Mairi (Auckland University of Technology, 2014)
This creative thesis considers peoples’ stories. It reflects upon the lived experiences of certain New Zealand Maori and Scottish Highlanders and interprets their unique relationships with land. Conceptually, the thesis considers landscape as a palimpsest, or a site that contains layered evidence of human histories (Bender, 1998). In the project I search for traces of the past to ’see‘ the present more deeply. McIlwraith states, “The cultural landscape... is the product of innumerable, often anonymous stage hands, toiling over... centuries and creating the sets for a slow, powerful drama... Despite its apparent openness, however, the land only reluctantly answers our questions” (1997, pp. 1-5). Using interviews I recorded in New Zealand and Scotland, I interpret stories as short filmic portraits that seek to communicate the concept of layers of connection. I research the potential of this by building panoramic video strata, explore the use of sound, modes of projection and the creative potentials of the newly developed PanOptica software.
Keywords: Indigenous; Human ecology; Duthchas; Palimpsest; Panorama; Ultra-widescreen; Maori; Highland Scots; Land reform; Commons; Whenua; Papatuanuku